Mediastinal Neurofibroma Originating from the Pulmonary Branch of the Right Vagus Nerve in a Patient without von Recklinghausen Disease - Okamoto, Junichi; Kubokura, Hirotoshi; Ishii, Hideaki; Usuda, Jitsuo (The Thoracic and Cardiovascular Surgeon Reports, 2013)
Intrathoracic neurofibromas originating from the vagus nerve in patients without von Recklinghausen disease is rare and poses a problem in etiological diagnosis. Surgical resection is usually necessary for precise diagnosis of such tumors.We report the first case of a neurofibroma originating from the right pulmonary branch of the vagus nerve in a 34-year-old male without von Recklinghausen disease.The diagnosis was suggested by the radiological features and was confirmed histologically after resection.
Keywords: neurofibroma; vagus nerves; VATS